Fiscal Decentralization and Fiscal Policy Performance - Sow, Mousse (IMF Working Papers; Working Paper ;, 2017)
This paper explores the impact of fiscal decentralization on fiscal policy performance in a large sample of advanced and developing economies. The findings suggest that a larger share of decentralized expenditure is associated with a stronger fiscal balance; however, fiscal decentralization can lead to more pro-cyclical fiscal policy. Thus, the design and pace of fiscal decentralization need to be tailored to the specificities of the economy. Countries that have already established strong accountablity and budget management capacity at the local level can benefit from fiscal decentralization. In contrast, in economies prone to large volatility from internal and external shocks, the central government may need to retain a sufficient share of expenditure and revenue to conduct counter-cyclical policies. Finally, the pace of expenditure and revenue decentralization should be aligned.